Long term cognitive dysfunction among critical care survivors: associated factors and quality of life—a multicenter cohort study - Isabel Jesus Pereira; Mariana Santos; Daniel Sganzerla; Caroline Cabral Robinson; Denise de Souza; Renata Kochhann; Maicon Falavigna; Luis Azevedo; Fernando Bozza; Tarek Sharshar; Regis Goulart Rosa; Cristina Granja; et al. (Annals of Intensive Care, 2024)
Abstract Objectives To identify the prevalence and associated factors of cognitive dysfunction, 1 year after ICU discharge, among adult patients, and it´s relation with quality of life. Methods Multicenter, prospective cohort study including ICUs of 10 tertiary hospitals in Brazil, between May 2014 and December 2018. The patients included were 452 adult ICU survivors (median age 60; 47.6% women) with an ICU stay greater than 72 h. Results At 12 months after ICU discharge, a Montreal Cognitive Assessment (tMOCA) telephone score of less than 12 was defined as cognitive dysfunction. At 12 months, of the 452 ICU survivors who completed the cognitive evaluation 216 (47.8%) had cognitive dysfunction. In multivariable analyses, the factors associated with long-term (1-year) cognitive dysfunction were older age (Prevalence Ratio–PR = 1.44, P < 0.001), absence of higher education (PR = 2.81, P = 0.005), higher comorbidities on admission (PR = 1.089; P = 0.004) and delirium (PR = 1.13, P < 0.001). Health-related Quality of life (HRQoL), assessed by the mental and physical dimensions of the SF-12v2, was significantly better in patients without cognitive dysfunction (Mental SF-12v2 Mean difference = 2.54; CI 95%, − 4.80/− 0.28; p = 0.028 and Physical SF-12v2 Mean difference = − 2.85; CI 95%, − 5.20/− 0.50; P = 0.018). Conclusions Delirium was found to be the main modifiable predictor of long-term cognitive dysfunction in ICU survivors. Higher education consistently reduced the probability of having long-term cognitive dysfunction. Cognitive dysfunction significantly influenced patients’ quality of life, leading us to emphasize the importance of cognitive reserve for long-term prognosis after ICU discharge.